Platform-switching implants and bone preservation: A systematic review and meta-analysis - Santiago, J. F.; De Souza Batista, V. E. [UNESP]; Verri, F. R. [UNESP]; Honório, H. M.; De Mello, C. C. [UNESP]; Almeida, D.A.Df. [UNESP]; Pellizzer, E. P. [UNESP] (Elsevier, 2016)
The aim of this study was to perform a systematic review and meta-analysis to evaluate the possible benefits of platform-switching (PSW) implants when compared to regular platform (RP) implants in the categories of bone preservation and longevity. This systematic review and meta-analysis was performed in accordance with the PRISMA statement, PICO question, and Jadad scale. The relative risk (RR) of failure and the mean difference for marginal bone loss were calculated considering a confidence interval (CI) of 95%. Heterogeneity and subgroup analyses were performed, and funnel plots drawn. Twenty-five studies (17 randomized controlled trials (RCTs) and eight prospective studies) involving 1098 patients and 2310 implants were analysed. The meta-analysis revealed a significant reduction in crestal bone loss for PSW implants compared with RP implants (-0.41 mm, 95% CI -0.52 to -0.29, P < 0.00001). However, there was no statistically significant difference in implant failure (RR 1.10, 95% CI 0.6-2.02, P = 0.75). A reduction in bone loss with PSW implants was observed for the following subgroups: RCTs only, implants in the maxilla, and implants in the mandible. PSW implants presented lower bone resorption compared with RP implants. RCTs should be done to explain the possible biases.
Keywords: alveolar bone loss; dental implant platform switching; dental implants; meta-analysis; review